Inovação tecnológica na pesquisa de demanda turística - Marra, Ana Laura de Oliveira (Universidade Federal de São Carlos, 2024)
This research aimed to identify the diversity of variables that make up the collection of tourism demand research data and the identification of criteria that favor demand research in a technological system, in the Immediate Region of Bragança Paulista (RIBP) and in the Metropolitan Region of São Paulo. Paulo (RMSP). This is a case study of demand research, which was developed based on deductive research, with a qualitative approach, of an interdisciplinary and exploratory-descriptive nature and which used the techniques of documentary, bibliographical research and semi-structured interviews to detailed investigation of the variables used in tourist demand surveys applied in three tourist cities: Atibaia, Bragança Paulista and Mairiporã, components of the sample of this study. The selection of informants was carried out through probabilistic, intentional sampling and/or using the snowball technique, among public servants and/or political agents who work in the public sector with tourism planning and development. The purpose was to understand the advances and particularities of research on tourist demand, which represents an essential study to understand the behaviors, 4 preferences and characteristics of visitors in a specific region or destination and, therefore, design coherent and effective public policy proposals, positioning and marketing of destinations in the tourist market. Furthermore, this work addresses current gaps and challenges related to implementing this research at the municipal level. The object of analysis of this research focused on variables used in collecting data on tourist demand, in the period between 2000 and 2023, aiming to identify possibilities for improvement and opportunities for improvement in the conduct of tourist research, through the use of technological systems. To this end, contemporary tools were explored that can optimize both data collection and processing, with the aim of achieving more effective results. References from scientific research carried out after the 2000s indicate that there are different methodologies used in demand research and that the Box-Jenkins methodology (Autoregressive Integrated Moving Average - ARIMA) is most frequently cited. Currently, this methodology has been combined with other methodologies and techniques, with the aim of expanding data collection and the scope of research. The variables used in research are not standardized and the presence of technology in data collection has become more common since 2014. It is estimated that the development of this research will contribute to filling research gaps regarding research tourist demand, at the municipal level, especially considering the support of technological systems, as well as for the formulation of public policies and more efficient State action and, also, with processes of technological innovation in the public management of tourism and the promotion of diversified tourist markets.
Technological innovation in tourist demand research
Keywords: Políticas Públicas; Demanda; Demanda turística; Sistemas Tecnológicos; São Paulo; Public Policy; Tourism Demand; Demand; Technological Systems; CIENCIAS SOCIAIS APLICADAS::TURISMO